Evaluating Mass Loss of Rubber Veneer after Thermal-Treatment and Rubber Laminated Veneer Lumber (LVL) Mechanical Properties - syvongsouk, khonexai (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to evaluate the mass loss of rubber wood veneer through thermal treatment and assess the bending strength of Laminated Veneer Lumber (LVL) produced from thermally treated rubber wood veneer. A 30-year-old rubber tree was cut into billets of 1300 mm in length, then peeled into veneers of 2.5 mm thickness using a spindleless lathe machine. The veneers were kiln-dried to a moisture content of 6–8%. Specimens measuring 2.5 × 400 × 400 mm were prepared for thermal treatment. The thermal treatment was carried out at three temperatures: 180°C, 200°C, and 220°C, each for three durations: 4, 12, and 20 minutes. After thermal treatment, the LVL panels were assembled using Urea-Formaldehyde (UF) adhesive. Specimens were cut for both edgewise and flatwise bending tests, and tested using a Universal Testing Machine (UTM) at a loading rate of 6 mm/s. Results indicated that both temperature and time significantly affected the mass loss of the veneer. As temperature and time increased, mass loss generally increased. The mass losses recorded were as follows: 180°C: 4 min – 9.21%, 12 min – 11.08%, 20 min – 9.92% 200°C: 4 min – 11.59%, 12 min – 11.29%, 20 min – 11.96% 220°C: 4 min – 13.01%, 12 min – 13.26%, 20 min – 14.22% Mechanical testing showed varying trends in Modulus of Elasticity (MOE) and Modulus of Rupture (MOR) underedgewise and flatwise conditions: Edgewise MOE: 180°C ≤ 200°C ≥ 220°C Flatwise MOE: 180°C ≥ 200°C ≥ 220°C Edgewise MOR: 180°C ≥ 200°C ≥ 220°C Flatwise MOR: 180°C ≤ 200°C ≥ 220°C These results suggest that thermal treatment conditions significantly influence both the mass loss and mechanical properties of LVL made from rubber wood veneer.